The Effect of Using Running Dictation Game Toward Students’ Comprehend in Reading Descriptive Text at The Eighth Grade Students of MTs Hubbulwathan Duri (International Journal of Business and Information Technology, 2023)
Based on the researcher observation, it was found that most of student cannot comprehend the reading materials well and their reading comprehension are still far from the expectation. And the major problem faced by them was found not interest in reading activity, and cannot answer the question after reading the descriptive text. So, the writer was interested in carrying out the reseach about this problem. The objective of the reseach is to find out the students’ comprehend in Descriptive text that taught by using Running Dictation game, to find out the students’ comprehend in Descriptive text that taught without using Running Dictation game and to find out whether there is any significant effect of using Running Dictation Game at the Eighth Grade Students’ of MTs Hubbulwathan Duri. The Subject was the Eighth Grade students’of MTs Hubbulwathan Duri, and the object of this research was the effect of using Running Dictation Game in Comprehend Descriptive text. The design of this research was Pre-Test Experimental. The Writer used one class as sample. That consists of 31 students in the class. The Writer gave pre-test to experimental class. Then, the writer gave treatment for experimental class. Finally, the writer gave post-test to experimental class in order to know the effect of Running Dictation Game that applied by the writer. The technique of collecting data was the test. The technique of analyzing data, the writer adopted paired sample t-test formula by using software SPSS V.17. After analyzing the data, the writer found that there is a significant effect of using Running Dictation game at the eighth grade students in Comprehend Descriptive text of MTs Hubbulwathan Duri.